2016
DOI: 10.1111/vsu.12445
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Functional Outcome of Tibial Tuberosity Advancement vs. Tibial Plateau Leveling Osteotomy and Extracapsular Repair in a Heterogeneous Population of Dogs

Abstract: At the walk, TTA achieves normal function by 12 months; however, at the trot TTA is indistinguishable from ECR. TPLO resulted in operated limb function that was similar to the control population by 6-12 months postoperatively at the walk and the trot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 40 publications
(102 reference statements)
5
89
1
9
Order By: Relevance
“…Authors of previous studies have reported that ground reaction forces were restored 6‐12 months after TPLO in dogs tested at the walk and trot. However, dogs treated with TTA produced normal ground reaction forces only at the walk at this time point . The average pet likely spends more hours in a day walking than trotting, and this level of activity may normalize CTOAM values; even joints with TTA behave differently at the trot.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Authors of previous studies have reported that ground reaction forces were restored 6‐12 months after TPLO in dogs tested at the walk and trot. However, dogs treated with TTA produced normal ground reaction forces only at the walk at this time point . The average pet likely spends more hours in a day walking than trotting, and this level of activity may normalize CTOAM values; even joints with TTA behave differently at the trot.…”
Section: Discussionmentioning
confidence: 86%
“…TPLO restores limb function at the walk and trot by 6‐12 months, according to gait kinematics. TTA achieves comparable function at the walk by 12 months but fails to match normal ground reaction forces at the trot . These functional metrics serve as indicators of the clinical performance of the procedure, but they do not test joint response to the biomechanical alterations induced by TPLO and TTA.…”
Section: Introductionmentioning
confidence: 99%
“…Usually the CrCL rupture occurs without major trauma and is thought to result from progressive degenerative changes in the substance of the CrCL 14. TPLO is the preferred technique of many orthopaedic surgeons internationally,15 16 and the long-term outcomes have been reported to be superior for TPLO versus Tibial Tuberosity Advancement (TTA) and extracapsular suture 17. This technique had resulted in an excellent outcome in this patient for contralateral CrCL rupture approximately two years previously.…”
Section: Discussionmentioning
confidence: 83%
“…Surgical procedures that actively stabilize the cruciate ligament deficient stifle can be divided into those that eliminate the cranial tibiofemoral shear force by decreasing the angle of the tibial plateau, by advancing the insertion of the quadriceps, or by a combination of both procedures . No single procedure has yet been established as vastly superior to another, and a favourable long‐term clinical outcome can be expected regardless of the technique chosen …”
Section: Introductionmentioning
confidence: 99%